Differences in Urea And Creatinine Levels in St-Elevation Myocardial Infarction (STEMI) And Non-St-Elevation Myocardial Infarction (NSTEMI) at Dr. Doris Sylvanus Hospital - Mallewa, Nurul Ilmi; Patricia, Tisha; Frethernety, Agnes; Permatasari, Silvani; Shinta, Herlina Eka (Fakultas Kedokteran Universitas Palangka Raya, 2025)
Acute Kidney Injury (AKI) in Acute Myocardial Infarction (AMI) patients occurs due to decreased blood flow to the kidneys. Decreased blood flow caused by blockage in coronary arteries of AMI patients both in ST-Elevation Myocardial Infarction (STEMI) and Non-ST-Elevation Myocardial Infarction (NSTEMI) which causes reduced blood flow so the oxygen supply carried by the blood to the myocardium is reduced. Decreased oxygen supply to myocardium reduces the heart's ability to pump blood throughout the body including to kidneys. Decreased blood flow to kidneys results decreased kidney function. Laboratory examination parameters commonly used to assess kidney function are urea and creatinine. This study aims to determine the differences urea and creatinine levels in STEMI and NSTEMI patients. This research method uses analytical observation with cross-sectional approach. Data urea and creatinine levels taken from medical records using a purposive sampling technique. Samples in this study was 170 people. Data analysis using the manwhitney test and the results of comparison of urea levels in STEMI and NSTEMI patients with a p value = 0.416 and for creatinine levels with a p value = 0.756. This means that there is no significant difference between urea and creatinine levels in STEMI and NSTEMI patients.